A study on effect of cutting conditions on surface finish in diamond turning process. (2015) - Vinod, Prakash; Rao, Charitha M.; Narendranath, S.; Kumar, P.V. Shashi
The single-point diamond turning (SPDT) process is capable of producing components with micrometre to submicrometre form accuracy and surface roughness in the nanometre range. The superior surface finish and form accuracy of SPDT allow the technology to be adopted widely for the manufacture of variety of precision mechanical and optical parts. However, the process parameters play an important role in obtaining desired higher surface finish. In this research work, Taguchi's orthogonal array is used for optimisation of process parameters of aluminium 6061 T6 material using an ultra-precision turning machine. The response variables measured to perform the analysis are surface roughness and vibration. The prediction of surface roughness has been carried by multiple regression analysis and artificial neural network techniques (ANN). A module has been developed and integrated with the machine for in-process estimation of surface finish using ANN.